2022
DOI: 10.5194/amt-15-4709-2022
|View full text |Cite
|
Sign up to set email alerts
|

Balloon-borne aerosol–cloud interaction studies (BACIS): field campaigns to understand and quantify aerosol effects on clouds

Abstract: Abstract. A better understanding of aerosol–cloud interaction processes is important to quantify the role of clouds and aerosols on the climate system. There have been significant efforts to explain the ways aerosols modulate cloud properties. However, from the observational point of view, it is indeed challenging to observe and/or verify some of these processes because no single instrument or platform has been proven to be sufficient. Discrimination between aerosol and cloud is vital for the quantification of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…There are differences in ACIs among different cloud phases. Due to the less complex microphysical processes in liquid-phase clouds, which do not involve mixed-phase and ice-phase processes, there have been many research findings on the interaction between aerosols and liquid-phase clouds [9,12,[19][20][21][22][23][24][25][26][27][28]. Numerous studies have found a negative correlation between cloud droplet size and aerosol concentration in liquid-phase clouds, consistent with the traditional aerosol indirect effect or "Twomey effect" by using satellites, aircraft, ground-based observations, etc.…”
Section: Introductionmentioning
confidence: 69%
“…There are differences in ACIs among different cloud phases. Due to the less complex microphysical processes in liquid-phase clouds, which do not involve mixed-phase and ice-phase processes, there have been many research findings on the interaction between aerosols and liquid-phase clouds [9,12,[19][20][21][22][23][24][25][26][27][28]. Numerous studies have found a negative correlation between cloud droplet size and aerosol concentration in liquid-phase clouds, consistent with the traditional aerosol indirect effect or "Twomey effect" by using satellites, aircraft, ground-based observations, etc.…”
Section: Introductionmentioning
confidence: 69%
“…Therefore, the combination of the two time series reduces the limitations of the instruments taken individually. Finally, the aerosol-cloud interaction intrinsically analyzed by STIA have important and multidisciplinary scientific implications, also in relation to the Earth's climate and its changes, as demonstrated by numerous publications [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Methods Detailsmentioning
confidence: 99%